Dampak Kebijakan Perubahan Kurikulum Merdeka di Sekolah Dasar Bagi Guru dan Peserta Didik - Benedicta Dwi Adventyana; Euis Nur Amanah Asdiniah; Mae Afriliani; Magdalena Magdalena; Siti Fadia Nurul Fitri; Prihantini Prihantini (Journal on Education, 2024)
The Merdeka Curriculum is implemented with the aim of making learning relevant and creative in line with current developments and student needs. The main focus of this policy is to provide flexibility to schools and teachers in designing curricula that suit local needs and student characteristics. Teachers play an important role in implementing this curriculum, because they are expected to be able to adapt their teaching methods to suit the needs and potential of their students. Through this policy, teachers are encouraged to play a more active role in the learning planning process, create an inclusive learning environment, and utilize a variety of learning resources. Students are also at the heart of this policy, with an emphasis on developing 21st century skills such as creativity, collaboration, problem solving and critical thinking. By giving students the freedom to choose and design their own learning, we hope they will become more engaged and gain a deeper understanding. Therefore, This article examines the impact or implications of independent curriculum policies in this field.